Pengendalian Heat Stress Pada Tenaga Kerja di Bagian Furnace PT. X Pangkalpinang Bangka Belitung - Fajrianti, Gita; Shaluhiyah, Zahroh; Lestantyo, Daru (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2017)
Background: Comfortable workplace is one of the factors supporting morale. The work environment is hot and humid will reduce labor productivity, it will also have negative impacts on health and safety. Warmer temperatures result in lower performance primarily thinking. Decreased ability to think happened after the temperature has exceeded 32 0 C. The temperature within the furnace area of 34.9 0 C, which exceeds the standardized NAV of 30.5 0 C. The purpose of this is to research analyze control of heat stress on the workforce section furnace PT.X Pangkalpinang Bangka Belitung.Method: This study used a qualitative approach with in-depth interviews on 8 key informants, 5 labor section of the production and management 3. Analysis of the data using content analysis.Results: The results showed that all informants reveal the temperature within the furnace hot work area in accordance with the results of temperature measurements in the field at 34.9 0 C exceeds the threshold standardized, control heat stress with training (education or training on heat stress control and controlling the risk of heat stress) is not routinely executed, control with fluid replacement has been provided by the company but the rules and patterns of consumption have not been implemented, control with acclimatization yet implemented in the company.Keywords: heat stress, control, worker